Harga Yang Adil dalam Mekanisme Pasar dan Peran Pemerintah dalam Perspektif Islam - Mabarroh Azizah (Unisia, 2012)
This article focuses on the implementation of the just price in islamic perspective, in which government intervention can be tolerated in this context. It is important therefore to be discussed what is the Just price and also pricing theory in islamic point of view. This article concludes that the Just price is a fixed price, and it is also called as equal price. This price is resulted by a fair market, by a fair supply and demand. The participation of the state or government here will only be Justified when instability arises, then the government should determine the price to maintain the interests of public as well as avoiding hoarding and injustices.Key words: Just price, market mechanism, government